2013
DOI: 10.1007/s00267-013-0160-3
|View full text |Cite
|
Sign up to set email alerts
|

Light Availability Prevails Over Soil Fertility and Structure in the Performance of Asian Knotweeds on Riverbanks: New Management Perspectives

Abstract: Asian knotweeds (Fallopia spp.) are considered one of the world's most invasive species. Restoring habitats dominated by these exotic species requires a better understanding of the importance of abiotic factors controlling the invasive knotweeds performance. We used observational data obtained on the embankment of the Isère River (France) to study the performance of Fallopia spp. under different soil, light, and disturbance conditions. On the Isère riverbanks, light intensity assessed by light quantity transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…The strongest limitation on invasive species presence and richness was imposed by tree canopy cover-likely a proxy for light availability and temperature (Warren 2010a,b). Although some invasive species tolerate shade and invade beneath forest canopy (Martin et al 2009), invasive species generally are shade-intolerant, including the species studied here (Dommanget et al 2013;Marlor et al 2014;Phillips-Mao et al 2014). Lythrum and Phragmites presence decreased significantly in our plots with greater canopy coverage, but Alliaria presence actually increased.…”
Section: Resultsmentioning
confidence: 69%
“…The strongest limitation on invasive species presence and richness was imposed by tree canopy cover-likely a proxy for light availability and temperature (Warren 2010a,b). Although some invasive species tolerate shade and invade beneath forest canopy (Martin et al 2009), invasive species generally are shade-intolerant, including the species studied here (Dommanget et al 2013;Marlor et al 2014;Phillips-Mao et al 2014). Lythrum and Phragmites presence decreased significantly in our plots with greater canopy coverage, but Alliaria presence actually increased.…”
Section: Resultsmentioning
confidence: 69%
“…However, one of the major environmental factors that can control its performance is the availability of light. It affects the above- and below-ground biomass of knotweed directly by reducing its performance and, consequently, its invasiveness ( Dommanget et al, 2013 ; Dommanget et al, 2019 ). Specifically, the below-ground system of the knotweeds presents the majority of its biomass.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the effectiveness of different native riparian species when competing with IAPs. Dommanget et al (2013) found that the allelopathic effect of Fallopia japonica influenced the growth of Salicaceae species to a different degree and that the choice of resistant species could prove crucial for restoration success. In the present study, the effectiveness of a willow brush mattress (a frequent technique for controlling riverbank erosion) in combination with adapted management strategies was tested.…”
Section: Introductionmentioning
confidence: 99%